Does Delay in Taking the American Board of Physical Medicine and Rehabilitation Certification Examinations Affect Passing Rates?. (October 2016) - Robinson, Lawrence R.; Driscoll, Sherilyn; Sabharwal, Sunil; Raddatz, Mikaela; Chiodo, Anthony E.
ABSTRACT: Objectives: The objective of this study was to examine whether a delay in initially taking the Part I or Part II American Board of Physical Medicine and Rehabilitation certification examinations influences the score or passing rates of candidates and whether enrollment in a subspecialty fellowship influences performance on the Part II certification examination. Design: This was a retrospective review of first-time candidates taking the American Board of Physical Medicine and Rehabilitation initial certification examinations from 2010 to 2014. Results: Passing rates declined as candidates delayed the examination past the time of initial eligibility. Passing rates for Part I were as follows (mean [95% confidence interval]): no delay, 91% (89%–94%); 1-yr delay, 68% (56%–82%); and more that 2 yrs' delay, 59% (55%–68%). For Part II, passing rates were as follows: no delay, 90% (85%–94%); 1-yr delay, 83% (72%–94%); and more than 2 yrs' delay, 68% (50%–83%). Those completing an accredited fellowship performed better (92% pass rate) on the Part II examination than did those who did not (81% pass rate), but they also had higher final year evaluations from their residency program directors. Conclusions: It seems preferable to take both Part I and Part II examinations as soon as one is eligible. Enrollment in an accredited fellowship may be associated with a higher chance of passing the examination.